Resurfacing promotes antibacterial activity of a lipid A–binding nanobody - Angela C. O’Donnell; Xun Wang; Nikol Kadeřábková; Kyra E. Groover; Bethany C. Perez; Amanda Helms; Jennifer S. Brodbelt; Despoina A. I. Mavridou; Bryan W. Davies (Proceedings of the National Academy of Sciences, 2025)
Nanobodies have been pursued as candidates for antimicrobial design due to their small size and versatile binding capacities, but direct antibacterial activity of a nanobody has yet to be described. Here, we employed a bacterial surface display platform to screen a synthetic library of nanobody variants for antimicrobial potential. We identified a candidate that binds the essential lipid A component of gram-negative lipopolysaccharide. Nonetheless, this nanobody required a weakened outer membrane to access its target and elicit its toxic activity. Borrowing from observations of innate immune proteins, we found that resurfacing nanobodies with positively charged residues enabled them to bind and perturb the gram-negative outer membrane, but this alone was not sufficient for toxic activity. However, when we resurface our lipid A-targeting nanobody, it gained the ability to disrupt the outer membrane and enact its antibacterial function against wild-type bacteria. This development of a dual-function nanobody that can reach and bind previously inaccessible gram-negative targets introduces a route for antimicrobial biologic advancement.